1982
DOI: 10.1002/app.1982.070270619
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of photosensitive rubbers. II. Photosensitivity of cyclized polydienes and polypentenamer with pendent cinnamate groups

Abstract: SynopsisPhotosensitivity of cyclized polydienes such as cis-1,4-polybutadiene, 1,2-polybutadiene, and polypentenamer having pendent cinnamate groups has been studied in terms of the influence of polymer structure. The photosensitivity, which was based on the photodimerization of cinnamate groups in these polymers, was greatly affected by the mobility of the cinnamate groups. The observed rates (k&) could be estimated by using the reciprocal of the difference between an irradiated temperature (T) and a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…The quality of curve fitting is conveyed in Figure 5, which also reveals the failure of simple first-and second-order reactions without exp(-t/τ) 40,41 to capture the asymptotic behavior in X. …”
Section: Chart 1 Polymers Monomers and Dimers I And Ii Synthesizedmentioning
confidence: 99%
“…The quality of curve fitting is conveyed in Figure 5, which also reveals the failure of simple first-and second-order reactions without exp(-t/τ) 40,41 to capture the asymptotic behavior in X. …”
Section: Chart 1 Polymers Monomers and Dimers I And Ii Synthesizedmentioning
confidence: 99%
“…4,5 It has been found that chains and present some characteristics of microphase separation. small variations in the polymer structure may promote expressive changes in chain mobility, 17,18 In the solid state, the behavior to be expected 5268 / 8E45$$5268 05-16-98 10:56:03 polaal W: Poly Applied …”
Section: Resultsmentioning
confidence: 98%
“…The maleic residues were then esterified behavior with chemical structure. [3][4][5] One of the with glycol cinnamates, giving rise to half-esters, features required to improve reactivity seems to in which the cinnamate groups were separated be chain mobility. In this regard, polydienes have from the main chain by segments of different lengths.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We had revealed the dependence of the photosensitivity on the glass-transition temperature of the polymer theoretically and experimentally in the case of the cyclized polydiene rubbers and linear polydiene rubbers having cinnamate groups. [12][13][14][15] This paper describes the synthetic conditions of a new type of photoresist by means of the reaction of polybutadiene and polypentenamer with various chloroacetic acids, and also the influence of the polymer structure on the photosensitivity of chloroacetylated polybutadiene in terms of the glass transition temperature of the polymer.…”
Section: Introductionmentioning
confidence: 99%